Análisis de los sílabos de lectura y escritura para el diseño de un Centro de Escritura Digital - Gerzon Yair Calle Álvarez; Dora Inés Chaverra Fernández (Mundo Fesc)
The teaching and learning of academic reading and writing continue to be of interest in university education, due to their contributions to access to disciplinary knowledge and the construction of a scientific community. The purpose of this article is to analyze reading and writing syllabi from the perspective of their contributions to the linguistic and didactic components for the design of a Digital Writing Center. The method used was a case study. A documentary review was conducted using a syllabus verification matrix from three sections of the University of Antioquia, Colombia. The sample consisted of 52 syllabi. A database was created in Microsoft Excel for frequency analysis and category relationships. The results show that the most frequently used term is reading and writing, and that all syllabi have a practical component of language use. It is concluded that a Digital Writing Center contributes to the integration of students into academic and scientific discourses, which have been developed in courses with an emphasis on reading and writing.